Analysis of Translation Techniques For "Who I Am" Lyrics From Putri Ariani Ft. Alan Walker Song - Surayya, Azizah; Wahyuni, Larasati Dwi; Rasisa Rahmi Nasution (Philosophiamundi, 2024)
This study aims to determine what techniques are used in the process of translating the lyrics of the song "Who I Am" by Putri Ariani ft. Alan Walker. The research method used is descriptive qualitative and uses translation theory, which Molina and Albir classified. Researchers found that literal translation techniques were used 11 times (52.38%), adaptation techniques were used 6 times (27.27%), modulation techniques were used 4 times (18.18%), and other techniques were used in smaller quantities.